Gouty Panniculitis with Ulcerations in a Patient with Multiple Organ Dysfunctions - Lu Wang; Crystal Rose; Paul Mellen; George Branam; Maria M. Picken (Case Reports in Rheumatology)
Gouty panniculitis is a rare manifestation of gout. Clinically, it is characterized by indurated subcutaneous nodules in nonjoint areas. Pathologically, typical characteristic gouty tophi can be seen in subcutaneous tissue. It is postulated that gouty panniculitis develops as a consequence of uric acid accumulation in the body and localized inflammatory changes in subcutaneous tissue. We report a case of a 46-year-old man with 20-year history of gout, who developed multiple subcutaneous nodules over the abdomen and right groin/thigh area over a 2-year period. After a recent episode of congestive heart failure and acute renal failure, the nodules increased in size and the overlying skin became erythematous and ulcerated. Pathologic examination demonstrated typical tophi in the dermis and subcutaneous tissue. A review of the literature yielded fifteen similar cases that had been previously reported. We conclude that gouty panniculitis may be a manifestation of undertreated gout and may be exacerbated by the deterioration of other systemic functions.